(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Earth has been under the control of diabetes for a very long time. Serious health hazards are posed by chronic diseases. If insulin production is impaired, the body will not be able to break down glucose, leading to diabetes. Over time, the accumulation of carbohydrates becomes harmful because the body fights against processing the glucose that it consumes. Symptoms include over-urination, thirst, hunger, and exhaustion. This type of diabetes is common in children and adults (specifically, those between the ages of 14 and 20), according to recent research. Both type 1 and type 2 diabetes exist. Insulin insufficiency causes type 1 diabetes, which is contracted during adulthood. Be that how it may, genetic type 2 diabetes can linger for quite some time. Health care technology has made the world a better place. While medications can help manage diabetes, it is still imperative that people with the disease take responsibility for their own health. A wide variety of online tools can detect diabetes, show insulin levels and risk, help people develop healthy routines to lessen the disease’s impact, and create personalized programs for nutrition and physical activity to enhance their lives. Because they offer trustworthy health care support, these apps are vital. Using these materials, we want to create an app for managing diabetes that is easy for everyone to use.